The association between household debt and marriage satisfaction in the context of urban household in Klang Valley, Malaysia - Cai, Yunchao; Abdullah Yusof, Selamah; Mohd Amin, Ruzita; Mohd Arshad, Mohd Nahar (UiTM Press, Universiti Teknologi MARA, 2020)
By using the data collected from urban households in Klang Valley, Malaysia, this study tries to provide empirical evidence on the effect of household debt on married Malaysian couples on their marital satisfaction. This study wishes to extend the implications of household debt in Malaysia beyond economic concern per se. We found that household debt does have a negative association with marriage satisfaction for married couples in Klang Valley Malaysia. Such relationship is valid even financial wellness and other demographic variables are controlled. Moreover, the less secured personal debt shows a significant negative relationship with the couple’s marriage satisfaction compared with no evidence on the impact of housing loan.